Mechanism-based targeting of cardiac arrhythmias by phytochemicals and medicinal herbs: A comprehensive review of preclinical and clinical evidence - Soltani, Danesh; Azizi, Bayan; Rahimi, Roja; Talasaz, Azita H.; Rezaeizadeh, Hossein; Vasheghani-Farahani, Ali (Frontiers in Cardiovascular Medicine, 2022)
Cardiac arrhythmias, characterized by an irregular heartbeat, are associated with high mortality and morbidity. Because of the narrow therapeutic window of antiarrhythmic drugs (AADs), the management of arrhythmia is still challenging. Therefore, searching for new safe, and effective therapeutic options is unavoidable. In this study, the antiarrhythmic effects of medicinal plants and their active constituents were systematically reviewed to introduce some possible candidates for mechanism-based targeting of cardiac arrhythmias. PubMed, Embase, and Cochrane library were searched from inception to June 2021 to find the plant extracts, phytochemicals, and multi-component herbal preparations with antiarrhythmic activities. From 7337 identified results, 57 original studies consisting of 49 preclinical and eight clinical studies were finally included. Three plant extracts, eight multi-component herbal preparations, and 26 phytochemicals were found to have antiarrhythmic effects mostly mediated by affecting K+ channels, followed by modulating Ca2+ channels, upstream target pathways, Nav channels, gap junction channels, and autonomic receptors. The most investigated medicinal plants were Rhodiola crenulata and Vitis vinifera. Resveratrol, Oxymatrine, and Curcumin were the most studied phytochemicals found to have multiple mechanisms of antiarrhythmic action. This review emphasized the importance of research on the cardioprotective effect of medicinal plants and their bioactive compounds to guide the future development of new AADs. The most prevalent limitation of the studies was their unqualified methodology. Thus, future well-designed experimental and clinical studies are necessary to provide more reliable evidence.